Reflection on learning of students of the fifth year of high school from Lima Metropolitana - Escurra Mayaute, Luis Miguel (2002)
It was studied the reflection in learning in high school students of the city of Lima, Peru. The participants were a random sample of 942 students, belonging to the school districts (USE) of Lima. The results of the psychometric analysis allows to state that content validity was obtained, the construct validity was calculated using the factorial confirmatory analysis, and the item-test relationship showed the reliability of the Reflection in Learning Profile (ERA-2001). The results show that the scores in the Reflection in Learning Profile in high school students have a tendency to normal distribution. The analysis indicate that the students of high school do not use in a significant way the reflection in learning. The comparison by kind of school indicate that the students of private schools show better integration, monitoring and reflection in learning. The comparison by gender points out that male students have a better integration and reflection on learning than their counterparts, this is, female students. Also, it was observed no statistical differences neither considering age, nor residence place.